Implementasi Kebijakan Satgas Adminduk dalam Meningkatkan Pelayanan Administrasi Kependudukan di Desa Lojejer Kabupaten Jember - Najib, Dhimas Ainun; Adawiyah, Putri Robiatul (Indonesian Journal Publisher, 2023)
This research aims to describe and analyze the implementation of the Adminduk Task Force policy in improving administrative services in Lojejer Village, Jember Regency. The research method used is a qualitative method with a descriptive approach. Data collection was carried out using observation, interviews and documentation techniques. The Lojejer Village Government through the Lojejer Village Head Decree Number: 141/10/35.09.11.01/2021 established a population administration service through the Population Administration Task Force to answer every public complaint regarding population documents. Lojejer Village is working on a population administration service to provide solutions to all population administration problems complained about by the community by creating a population administration service with a pick-up-ball concept through the Population Administration Task Force. Based on the research results, the implementation of the Adminduk Task Force's policy in improving services in Lojejer Village with four variables including communication, resources, disposition and organizational structure is going well, but it is necessary to carry out socialization regarding the Adminduk Task Force so that the community is able to understand things related to administrative services. And the Chair of the Adminduk Task Force must consider the small honorarium for members of the Adminduk Task Force so that the Adminduk Task Force's services run well.